2022
DOI: 10.1186/s43094-022-00416-6
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect of Apium graveolens & curcumin against Non-alcoholic fatty liver disease induced by high fructose-high fat diet in rats

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is a condition resulting from fat aggregates in liver cells and is associated with metabolic syndrome, obesity, and oxidative stress. The present work was designed to investigate the role of celery and curcumin against high-fructose–high-fat (HFHF) diet-induced NAFLD in rats. Thirty male rats were classified into five groups: GP1: control group (rats were fed a normal control diet), GP2: HFHF group as a positive control (rats were fed a HFHF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
0
1
Order By: Relevance
“…Many studies have linked high-fat, high-fructose diets with the development of glucose intolerance and insulin resistance [ 44 , 45 ]. Although our results did not reveal significant alternations in fasting blood glucose and insulin levels (in contrast to some other studies [ 46 , 47 ]), we found that the HFF diet increased glucose excursion during the IPGTT. To our knowledge, this is the first study that demonstrated decreased systemic insulin sensitivity and glucose intolerance after the HFF + cholic acid diet.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies have linked high-fat, high-fructose diets with the development of glucose intolerance and insulin resistance [ 44 , 45 ]. Although our results did not reveal significant alternations in fasting blood glucose and insulin levels (in contrast to some other studies [ 46 , 47 ]), we found that the HFF diet increased glucose excursion during the IPGTT. To our knowledge, this is the first study that demonstrated decreased systemic insulin sensitivity and glucose intolerance after the HFF + cholic acid diet.…”
Section: Discussioncontrasting
confidence: 99%
“…The animal species involved were Sprague-Dawley rats, C57BL/6 mice, Albino rats, and C57BL/6J ob/ob mice. A total of 15 studies (Cunningham et al, 2018;Ding et al, 2018;Li et al, 2018;Yan et al, 2018;Mahmoud et al, 2018;Feng et al, 2018;Feng et al, 2019;Gheibi et al, 2019;Lee et al, 2020;Li et al, 2021;Liu et al, 2017;Abd El-Hameed et al, 2021;Sun et al, 2021;Chen et al, 2022;Abd-Elrazek et al, 2022) reported that a high-fat diet (HFD) model was established, 4 studies (Wan et al, 2014;Kim et al, 2016;Tong et al, 2021;Lee et al, 2022) used a methionine-choline-deficient diet (MCD) model, and only 1 study (Kuo et al, 2012) used C57BL/6J ob/ob mice as an obesity model (Figure 1). The duration of the administration varied from 2 weeks to 16 weeks, and the dosage ranged from 50 mg/kg to 200 mg/kg.…”
Section: Characteristics Of Studies Included In the Analysismentioning
confidence: 99%